Digital Transformation of BPJS Ketenagakerjaan: Innovations in JMO, E-Money, and SMILE to Enhance Service Effectiveness and Responsiveness - Zulkifli, Afni; Herlinda, Dwi; Ruslyhardy, Ruslyhardy; Rifaldi, M; Marshanda, Yohana Widya (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2024)
The digital transformation of BPJS Ketenagakerjaan has significantly improved service efficiency and accessibility through the implementation of Jamsostek Mobile (JMO), E-Money, and the SMILE system. The JMO application streamlines Old Age Security (JHT) claims, allowing participants to process their benefits faster and more conveniently. The integration of E-Money simplifies contribution payments via mobile banking, QRIS, and digital wallets, reducing reliance on manual transactions. The SMILE system (Service, Memorable, Integrity, Loyal, and Excellent) enhances service professionalism and responsiveness, ensuring a positive participant experience. Additionally, WA SMILE optimizes contribution collection efforts, providing direct engagement and timely payment reminders. These innovations reduce administrative delays, improve service delivery, and strengthen participant trust. To sustain these improvements, continuous system upgrades, digital literacy initiatives, and cybersecurity measures are essential. BPJS Ketenagakerjaan’s commitment to digital innovation ensures an inclusive, efficient, and reliable social security service, reinforcing its role as a pioneering institution in public service modernization.